Cultural Content Analysis of English Textbooks for Senior High School Grade XI - Plasita Agesti; Etika Rachmawati (Universitas Galuh, 2023)
To master a language, we must become familiar with its culture as well; for that reason, incorporating cultural content into them is crucial. But, this matter seems to have been neglected by teachers when choosing English textbooks since there are many sources of English textbooks nowadays. Thus, this study aims to determine the types of culture and determine the representation of culture in terms of four senses of culture in Bahasa Inggris XI and Bupena English for SMA/MA Grade XI. The data were collected by using two adapted checklists designed by Najmiatul Fauza (2018) and Ibnu Mustofa (2019). The findings revealed that in Bahasa Inggris XI target culture was presented predominantly and in the other book the most presented type of culture is source culture. This implies that the target culture is more exposed in Bahasa Inggris for Grade XI, whereas the source culture is more exposed in the other book. Regarding the representation of culture in terms of four senses of culture, Bupena English for SMA/MA Grade XI placed a greater emphasis on the representation of pragmatics sense, meanwhile, Bahasa Inggris XI focused more on the sociological sense. Similarly, neither of the English textbooks had any representation of the semantic sense. Finally, English textbooks should give more culturally diverse content at which each type of culture and each type of sense should be equally represented. Students’ awareness of the existence of other cultures will aid them in mastering the language.